"All the famous deeds of Achilles are yours": homeric exemplarity in late antique panegyric - Hadjittofi, Fotini (2022)
Late antique panegyrists often raise up their laudandi by casting a shadow on Homer and his (mainly Iliadic) heroes. This paper traces the history of an increasingly irreverent attitude towards Greece’s foundational poet and his heroes within panegyric compositions and asks what motivates this flamboyant rejection. The impact of a Christian mode of exemplarity is incontestable, but cannot wholly account for this development. Christian encomia which engage the Hebrew Bible for their synkriseis generally shy away from undercutting the venerable biblical exempla. My suggestion is that the “aggressive” attitude towards Iliadic exempla in classicizing panegyric is bound up with the position of the Iliad as the didactic text par excellence and as a central, yet deeply problematic, text in debates around ideal rulership.